PENGARUH GOOD CORPORATE GOVERNANCE, CORPORATE SOCIAL RESPONSIBILITY, INTELLECTUAL CAPITAL DAN GREEN BANKING TERHADAP NILAI PERUSAHAAN - Nethania Angelika Lipazya; Hermie Hermie (EBID: Ekonomi Bisnis Digital, 2024)
The implementation of this research is aimed at evaluating the value of banking companies from 2020 to 2022 that have been listed on the Indonesia Stock Exchange as a result of being influenced by green banking, intellectual capital, corporate social responsibility, and good corporate governance. The data implemented in the study is in the form of sustainability and annual report data available on the official websites of each company and the IDX. The population applied in the study amounted to 47 banking companies. The number of samples used was 36 banking companies selected by applying a purposive sampling method based on certain criteria. The data analysis method applies Eviews-assisted panel data regression analysis. Based on data processing and analysis, it is obtained that corporate governance affects the value of banking companies. While green banking, intellectual capital, and corporate social responsibility do not affect the value of banking companies.